Atypical Large Scrotal Angiokeratomas Treated with Long-Pulse Alexandrite Laser - Molla A (Dove Medical Press, 2024)
Amr Molla Department of Medicine, College of Medicine, Taibah University, Madinah, Saudi ArabiaCorrespondence: Amr Molla, Dermatology, Dermatologic Surgery & Lasers, Universities Road, P.O. Box: 344, Taibah, Madinah, 42353, Saudi Arabia, Tel +966504342992, Email amolla@taibahu.edu.saBackground: Fordyce angiokeratoma, a benign tiny lesion usually on the scrotum, increases with age and may cause symptoms like itching and bleeding in nearly half of the cases. Although treatment is not always necessary, it is primarily considered for cosmetic reasons in the case of larger or atypical lesions.Case Report: We present the case of a healthy adult male with multiple large red-blue hyperkeratotic nodules and papules on his scrotal skin, causing bleeding upon minor trauma and personal embarrassment. After confirming the diagnosis of angiokeratomas of the scrotum through histopathology, the patient underwent two sessions of Long-Pulse Alexandrite Laser treatment, resulting in a 90% reduction in lesions, no scrotal bleeding, and a satisfactory cosmetic outcome.Conclusion: The Long-Pulse Alexandrite Laser is a precise and effective treatment for vascular lesions, like angiokeratomas, offering customizable parameters. However, patient-specific factors and careful evaluation are essential, recognizing the laser's limitations for optimal results.Keywords: angiokeratomas, Fordyce angiokeratoma, Alexandrite laser, 755 nm, case report